2015
DOI: 10.1039/c4sc02554g
|View full text |Cite
|
Sign up to set email alerts
|

A strategy based on nucleotide specificity leads to a subfamily-selective and cell-active inhibitor of N6-methyladenosine demethylase FTO

Abstract: The AlkB family of nucleic acid demethylases are of intense biological and medical interest. The discovery of a highly selective FTO inhibitor should greatly facilitate the study of these enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 43 publications
4
131
0
Order By: Relevance
“…To the best of our knowledge, this study represents not only the first example of multiprotein DCC, but also an ew strategy for probingd ynamic chemicals ystems, which will hopefully furthero ur understanding of protein-directed self-assembly, and inspiren ew applications for DCC-based approaches. [53] )and ALKBH3( salmonsurface and salmons ticks;PDB ID 2IUW [54] ). The rightp anels show close-up views of interactions between 7 and active-site residues in FTO and ALKBH3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this study represents not only the first example of multiprotein DCC, but also an ew strategy for probingd ynamic chemicals ystems, which will hopefully furthero ur understanding of protein-directed self-assembly, and inspiren ew applications for DCC-based approaches. [53] )and ALKBH3( salmonsurface and salmons ticks;PDB ID 2IUW [54] ). The rightp anels show close-up views of interactions between 7 and active-site residues in FTO and ALKBH3.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our detection strategy,t here was also am arked separation of individual meltingp eaks (DT m > 9 8C), whiche nabled any ligand-induced T m shift to be clearly detected without merging of peaks, as demonstrated by ligand binding experiments with 1 (a known generic inhibitor of AlkB subfamilies) [57] and FTO-selective inhibitor 2 (PubChem ID:1 26970771;F igure 3C and D). [53] By comparison, DSF analysis of am ixture of untagged ALKBH5, FTO, and ALKBH3 produced an overlapping melting profile that was difficult to deconvolute( Figure 3E). Thus, the combined use of thermalt ags with DSF enables the simultaneous analysiso fd ifferent fusion proteins in am ixture, even structurally similars ubfamily members,w hich is otherwise challenging to differentiate.…”
Section: Recognition and Analysis Of Multiple Proteins In Am Ixture Bmentioning
confidence: 97%
See 2 more Smart Citations
“…FTO inhibitors have been reported, such as rhein, α‐ketoglutarate (αKG) analogues, meclofenamic acid, radicicol, and so on . Previous work in our group showed that 4‐chloro‐6‐(6'‐chloro‐7'‐hydroxy‐2',4',4,‐trimethyl‐chroman‐2'‐yl)benzene‐1,3‐diol (CHTB) and N‐(5‐chloro‐2,4‐dihydroxyphenyl)‐1‐phenylcyclobutanecarboxamide (N‐CDPCB) are inhibitors of FTO .…”
Section: Introductionmentioning
confidence: 99%